Competition of calcified calmodulin N lobe and PIP(2) to an LQT mutation site in Kv7.1 channel - Tobelaim, William Sam (Proc Natl Acad Sci U S A, 2017)
Voltage-gated potassium 7.1 (Kv7.1) channel and KCNE1 protein coassembly forms the slow potassium current I(KS) that repolarizes the cardiac action potential. The physiological importance of the I(KS) channel is underscored by the existence of mutations in human Kv7.1 and KCNE1 genes, which cause cardiac arrhythmias, such as the long-QT syndrome (LQT) and atrial fibrillation. The proximal Kv7.1 C terminus (CT) binds calmodulin (CaM) and phosphatidylinositol-4,5-bisphosphate (PIP(2)), but the role of CaM in channel function is still unclear, and its possible interaction with PIP(2) is unknown. Our recent crystallographic study showed that CaM embraces helices A and B with the apo C lobe and calcified N lobe, respectively. Here, we reveal the competition of PIP(2) and the calcified CaM N lobe to a previously unidentified site in Kv7.1 helix B, also known to harbor an LQT mutation. Protein pulldown, molecular docking, molecular dynamics simulations, and patch-clamp recordings indicate that residues K526 and K527 in Kv7.1 helix B form a critical site where CaM competes with PIP(2) to stabilize the channel open state. Data indicate that both PIP(2) and Ca(2+)-CaM perform the same function on I(KS) channel gating by producing a left shift in the voltage dependence of activation. The LQT mutant K526E revealed a severely impaired channel function with a right shift in the voltage dependence of activation, a reduced current density, and insensitivity to gating modulation by Ca(2+)-CaM. The results suggest that, after receptor-mediated PIP(2) depletion and increased cytosolic Ca(2+), calcified CaM N lobe interacts with helix B in place of PIP(2) to limit excessive I(KS) current inhibition.